Towards customized heat treatments and mechanical properties in the LPBF-processed Ti-6Al-2Sn-4Zr-6Mo alloy. (March 2022) - Carrozza, Alessandro; Aversa, Alberta; Fino, Paolo; Lombardi, Mariangela
Graphical abstract: Highlights: The LPBF process induces the formation of softening α" orthorhombic martensite in the Ti-6Al-2Sn-4Zr-6Mo alloy. Distinct transformations occur at different annealing temperatures: α" decomposition, residual stress relaxation and β complete recrystallization. Post-processing heat treatments can be specifically tailored to tune the final microstructure/mechanical properties of the material. Optimal combinations of strength and ductility can be achieved. Abstract: The Ti-6Al-2Sn-4Zr-6Mo alloy was recently successfully processed using the laser powder bed fusion technology. This material is characterized by a very low strength in the as-built state, due to the presence of α" martensite. In this work, the transformations taking place at different temperatures in this alloy were investigated with the aim of achieving the necessary knowledge to customize the mechanical properties via heat treatments. Martensite decomposition, residual stress relaxation and the β-transus temperature were identified at progressively increasing temperatures. Then, different annealing treatments, corresponding to the temperatures identified, were conducted. For each condition, dissimilar α + β microstructures were obtained, varying in terms of morphology (lamellar, bi-lamellar) and size of the α laths (0.5–2.2 µm). The corresponding tensile properties were also significantly different. In particular, outstanding strength values were achieved when the residual stress was retained. For higher temperatures, a slight drop in strength was coupled with an outstanding improvement in terms of ductility. Overall, the most balanced combination of tensile properties was obtained for an annealing temperature of 875 °C. In this condition, the bi-lamellar microstructure grants a reduction in the slip length due to the presence of secondary α laths.